Energy, Hierarchy and the Origin of Inequality - Blair Fix (PLoS ONE, 2019)
Where should we look to understand the origin of inequality? I propose an unusual window of evidence—modern societies. I hypothesize that evidence for the origin of inequality is encoded in the institutional structure of industrial societies. To test this idea, I use a model to project modern trends into the past. This model takes the modern relation between energy, hierarchy, and inequality and creates a hindcast of the origin of inequality. The results are broadly consistent with the available evidence. The model predicts an explosion of inequality with the transition from hunter-gathering to agriculture, followed by a plateau. This finding potentially opens a new window of evidence into the origin of inequality.
Keywords: P18; P28; P48; Q4; D3; P16; 330; energy; hierarchy; inequality